2010
DOI: 10.1037/a0020080
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical framework for the study of adult cognitive plasticity.

Abstract: Does plasticity contribute to adult cognitive development, and if so, in what ways? The vague and overused concept of plasticity makes these controversial questions difficult to answer. In this article, we refine the notion of adult cognitive plasticity and sharpen its conceptual distinctiveness. According to our framework, adult cognitive plasticity is driven by a prolonged mismatch between functional organismic supplies and environmental demands and denotes the brain's capacity for anatomically implementing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
578
2
23

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 651 publications
(630 citation statements)
references
References 194 publications
(312 reference statements)
27
578
2
23
Order By: Relevance
“…The recent review, together with others (e.g., Hertzog et al, 2009;Lövdén et al, 2010;Noack et al, 2009;Klingberg, 2010;Shipstead et al, 2010;, revealed that some transfer is typically observed with training procedures targeting working memory, executive functioning, general cognitive ability, and other constructs. However, the validity of positive transfer depends on both theoretical and methodological considerations.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The recent review, together with others (e.g., Hertzog et al, 2009;Lövdén et al, 2010;Noack et al, 2009;Klingberg, 2010;Shipstead et al, 2010;, revealed that some transfer is typically observed with training procedures targeting working memory, executive functioning, general cognitive ability, and other constructs. However, the validity of positive transfer depends on both theoretical and methodological considerations.…”
Section: Resultsmentioning
confidence: 95%
“…This question is related to the old issue of separating task-specific from task-general effects of training (e.g. Baltes & Lindenberger, 1988;Lövdén et al, 2010). One way to answer this question is to try to determine and evaluate the distance of transfer tasks (Barnett & Ceci, 2002;Noack et al, 2009;Zelinski, 2009;cf.…”
Section: Generality Of Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, the present data set suggests that exposing participants to varying levels of difficulty is sufficient for challenging the flexibility of the cognitive system by exceeding routine demands (cf. Lövden, et al, 2010) and thereby inducing performance improvements.…”
Section: Resultsmentioning
confidence: 99%
“…OLM training may also be particularly successful in older adults because OLM relies heavily on the hippocampus (for a meta-analysis see Kessels, de Haan, Kappelle, & Postma, 2001; for reviews see Burgess, 2008;Postma, Kessels, & van Asselen, 2008), one of the most plastic brain regions up into old age (Goh & Park, 2009;Lövdén et al, 2010). To maximize the intervention's effectiveness, OLM training was both variable (by using three different tasks; Schmidt & Bjork, 1992) and adaptive (by adjusting task difficulty to individual performance; Klingberg, 2010, but see von Bastian & Eschen, 2016.…”
Section: The Present Studymentioning
confidence: 99%